PELAKSANAAN MAHAR DALAM PERKAWINAN ADAT MASYARAKAT MUNA (Sebuah Tinjauan Akomodasi Hukum) - Aris Nur Qadar Ar.Razak (Al-'Adl, 2018)
This study examines two aspects, first, the implementation of dowries in Muna custom marriage. Second, legal accommodation the implementation of traditional Muna community marriage dowry into the national legal system. The methodology aspect, this research includes normative-empirical research. The results showed: first, the implementation of dowries in Muna custom marriage is arranged based on social stratification by using the term boka and suku as the unit of value. The stratification group, namely kaomu (nobility) with a dowry of 20 boka, walaka 10boka 10 suku, anangkolaki 7 boka and 2 suku and maradika with dowry 3 boka and 2 suku. Second, the legal accommodation of Muna's customary duties of marriage is strived as a positiveization of the elements of the dowry procession into a product of legislation, such as the law. Putting the duty of Muna's customary marriage dowry into the law in addition to having a stronger legal force.